Report on the Types and Distribution of Antennal Sensilla in Lygaeidae (Heteroptera: Lygaeoidea) and Their Putative Functions - Agnieszka Nowińska (Insects)
Antennal sensillar structures respond to a variety of environmental stimuli. In the present study, the antennal sensilla of all three subfamilies of the family Lygaeidae are studied for the first time. This research shows the presence of five main types of sensilla (sensilla trichodea, chaetica, campaniformia, basiconica, and coeloconica). Their comparison to other, previously studied, heteropteran insects and their putative mechano-, chemo-, and thermo-hygroreceptive functions are discussed. The current study shows uniformity in the types of sensilla in all studied species. However, minor differences between the subfamilies, as well as within the subfamily Lygaeinae, are observed.